Anthropological dimensions as a predictor of specific motor skills of young water polo players - Aleksandrovic, M.; Jorgic, B.; Georgiev, G.; Ozsari, M.; Arslan, D. (Facta Universitatis: Series Physical Education and Sport, 2015)
The purpose of this study was to determine the common influence of anthropological dimensions on the specific motor skills of young water polo players. A total number of 90 water polo players were involved in the study. The investigation protocol consisted of standardized anthropometric measurements, functional and basic motor abilities and specific motor skills assessments. The general factor of specific motor skills in water polo was obtained by way of factorization and represents a criterion. The regression analysis showed that anthropological dimensions as group predictors, two variables of explosive power and one variable of repetitive torso strength as a separate variable have a significant influence on the general factor of specific motor skills. The results of the study pointed out the impact of anthropological dimensions on specific motor skills of selected young water polo players. This enables the proper selection process for young water polo players.